2021
DOI: 10.3390/su13094817
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Daily Behaviors Related to Health Risks of the Ger Residents in Ulaanbaatar, Mongolia

Abstract: The capital city in Mongolia comprises two types of dwellings: apartments and Gers. The Ger is a traditional Mongolian house. Residents of Ger districts in Ulaanbaatar use coal as a source of fuel for daily activities such as heating and cooking in winter due to lack of central heating systems. After coal burning, the ash deposited at the bottom of the oven converts into a powder containing heavy metals that are toxic to human health. Through questionnaires at sites where concentrations of heavy elements were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The division of residential areas into areas with multi-storey buildings and gers is such a unique Mongolian phenomenon that it is addressed in other studies. Coal is the primary energy source in ger areas, and burninggenerated ash is becoming one of the primary sources of in situ soil pollution due to improper disposal 45,46 . Kasimov et al 47 stated that the soils of the districts with multi-storey buildings are more polluted than the ger districts.…”
Section: Resultsmentioning
confidence: 99%
“…The division of residential areas into areas with multi-storey buildings and gers is such a unique Mongolian phenomenon that it is addressed in other studies. Coal is the primary energy source in ger areas, and burninggenerated ash is becoming one of the primary sources of in situ soil pollution due to improper disposal 45,46 . Kasimov et al 47 stated that the soils of the districts with multi-storey buildings are more polluted than the ger districts.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, dust may be inadvertently swallowed and easily adhere to children’s skin due to their proximity to the floor and their tendency to touch objects in addition to put their hands and other objects into their mouths (Latif et al 2014 ; Olujimi et al 2015 ). Studies on heavy metal pollution in house dust show that features such as the type of heating of houses (Battsengel et al 2021 ; Zhao et al 2020 ), the type of floor covering, traffic emissions (Capozzi et al 2019 ; Duan et al 2020 ; Hashemi et al 2020 ; Yap et al 2011 ), proximity to industrial areas (Yap et al 2011 ), wall paint type and colour (Hashemi et al 2020 ; Hassan 2012 ; Ogilo et al 2017 ), age of the building (Hassan 2012 ; Popoola et al 2012 ), and smoking habits (Hashemi et al 2020 ; Hassan 2012 ; Zhou et al 2020 ) may affect the concentrations of indoor heavy metal levels. Rasmussen et al ( 2001 ) found that indoor dust in electrically heated homes in Canada tends to have both mercury (Hg) and Pb contents higher than those heated by oil or gas.…”
Section: Introductionmentioning
confidence: 99%